Programmed death-ligand 1 (PD-L1) is expressed in a significant number of the uterine cervical carcinomas - Opal L. Reddy; Peter I. Shintaku; Neda A. Moatamed (BMC, 2017)
Abstract Background The programmed death-1/programmed death-ligand-1 (PD-1/PD-L1) immune regulatory axis has emerged as a promising new target for cancer therapeutics, with lasting responses seen in the treatment of metastatic renal and lung carcinomas, as well as melanomas. As tumor surface expression of PD-L1 has been found to correlate with objective responses to anti-PD-L1 immunotherapies, we investigated the expression of PD-L1 in human cervical tumors and provide an adopted scoring system for the systematic evaluation of PD-L1 staining. Methods Immunohistochemical staining for PD-L1 expression was performed on a tissue microarray of 101 normal and neoplastic cervical tissues. Neoplastic cores were divided into three groups: squamous cell carcinoma, adenosquamous carcinoma, and endocervical adenocarcinoma. PD-L1 expression was scored based on an adopted scoring system accounting to percentage and intensity of positivity, and results provided alongside available clinical and demographic data. Results Overall, PD-L1 was positive in 32 of 93 (34.4%) cervical carcinomas. Subcategorically, PD-L1 was positive in 28 of 74 (37.8%) squamous cell carcinomas, two of seven (28.6%) adenosquamous carcinomas, and two of 12 (16.7%) endocervical adenocarcinomas. It was negative in six benign cervical tissues. Conclusions This study shows a significant expression of PD-L1 in 34.4% of cervical carcinomas and no expression of PD-L1 in benign cervical tissues. These findings suggest a role for further investigation of anti-PD-L1/PD-1 immunotherapies in the treatment of PD-L1-positive cervical tumors. In addition, our adopted scoring system will facilitate more systematic correlations between tumor reactivity and response to treatment.